Functional dyspepsia susceptibility is related to CD14, GNB3, MIF, and TRPV1 gene polymorphisms in the Greek population - Triantafyllou, K.; Kourikou, A.; Gazouli, M.; Karamanolis, G. P.; Dimitriadis, G. D. (Neurogastroenterology and motility, 2017)
Background Functional dyspepsia (FD) susceptibility might be influenced by polymorphisms of genes related to inflammation (CD14, macrophage migration inhibitory factor [MIF]), motor (GNB3), and sensory dysfunction (GNB3, TRPV1). We examined the association between CD14 rs2569190, GNB3 rs5443, MIF rs222747, and TRPV1 rs755622 gene polymorphisms with FD (Rome III criteria) in the Greek population. Methods We genotyped 174 dyspeptics (115 with epigastric pain syndrome; 41% Helicobacter pylori positive) and 181 controls using polymerase chain reaction‐based methods and we measured disease symptoms’ burden with a modified Gastrointestinal Symptoms Related Scale. Key Results Homozygous for the TT genotype and the T allele of the CD14 gene were significantly associated (OR [95% CI]) with FD (2.65 [1.42–4.94] and 1.67 [1.23–2.26], respectively). The CT, TT genotypes, and T allele frequencies of GNB3 showed also significant association with FD (2.18 [1.35–3.54], 3.46 [1.30–9.23], and 2.18 [1.48–3.19]). While heterozygous GC MIF genotype was more common in dyspeptics (1.67 [1.07–2.60]), homozygous CC genotype and the C allele of TRPV1 gene were more prevalent in controls (0.47 [0.25–0.87] and 0.69 [0.51–0.92], respectively). None of the gene polymorphism was related either to dyspepsia clinical syndrome type or to the H. pylori infection. Among dyspeptics, CD14 TT genotype was related to lower epigastric pain burden score (p<.011); CD14 CT genotype was related to higher epigastric burning and nausea burden scores (p<.04) while belching score was lower (p=.027) in MIF CG dyspeptics. Conclusion & Inferences Functional dyspepsia susceptibility is related to CD14, GNB3, MIF, and TRPV1 gene polymorphisms, while CD14 and MIF gene variants are also associated with dyspepsia symptoms burden.